PENGARUH KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS PASIEN POLI GIGI DI PUSKESMAS GANTIWARNO KLATEN JAWA TENGAH - Wahyuni, Yuyun; Anggryani Solmares, Mathilda; Suliantoro (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Health centers are required to provide health services that meet optimal service standards. This is the accountability of other health centers. Health centers are declared successful, not only in terms of the completeness of the superior facilities, but also the attitude and services of human resources are elements that have a significant influence on the services produced and prepared by patients. This study aims to determine the significance of the influence of service quality and satisfaction on the loyalty of dental polyclinic patients at the Gantiwarno Klaten Health Center, Central Java. The population in this study were patients who had visited the dental polyclinic of the Gantiwarno Klaten Health Center, Central Java. The number of samples used was 100 respondents. Data processing used the SPSS analysis tool. Data analysis used in this study was quantitative using the multiple linear regression method. The results of this study indicate that the variables of service quality and satisfaction have a significant effect on the loyalty of dental polyclinic patients at the Gantiwarno Klaten Health Center, Central Java. The contribution (R2) of the variables in this study was 72.7%.